Structuring small firms for rapid growth - Fombrun, Charles J.; Wally, Stefan (Journal of Business Venturing, 1989)
Small firms confront significant dilemmas as they struggle to capitalize on growth opportunities. Surges in demand frequently result in the hiring of additional operating and administrative personnel. Rapid growth in employment, however, creates managerial problems whose resolution requires firms to design collateral systems that both mobilize staff attention toward a shared vision and support the firm's strategic outlook (Hambrick and Crozier 1985; Kotter and Sathe 1978). This article reports on a cross-sectional study of 95 small U.S. firms that experienced a five-year surge in growth. Findings indicate that the internal systems designed by these firms to support their rapid growth varied systematically by strategic orientation and degree of product diversity. Contrary to expectations, the relationship between strategy and structure failed to demonstrate a significant effect on these firms' levels of performance. Indeed, the data suggest that in fashioning these systems, firms' managements may, in fact, be responding to contradictory pulls. 1. Bureaucratization versus Decentralization. Increased hiring stimulates bureaucracy: firms formalize procedures as staffing doubles and triples. Employee participation and autonomy decline and internal labor markets develop. Tied to growth, however, is also an increased diversity in product offerings that favors less formalized decision processes, greater decentralization, and the recognition that the firm's existing human resources lack the necessary skills to manage the broadening portfolio. 2. Environment versus Strategy. High environmental turbulence and competitive conditions favor company cultures that support risk taking, autonomy, and employee participation in decision making. Firms confront competitors, however, through strategies whose implementation depends on the design of formal systems that inhibit risk taking and autonomy. 3. Strategic Emphases on Quality versus Cost versus Innovation. Rapidly growing firms strive to simultaneously control costs, enhance product quality, and improve product offerings. Minimizing costs and undercutting competitors' product prices, however, are best achieved by traditional hierarchical systems of decision making and evaluation that contrast with the kinds of autonomous processes most likely to encourage the pursuit of product quality and innovation. The findings suggest that managing surges in growth involves multiple challenges: resolving the stresses and strains induced by attempts to control costs while simultaneously enhancing quality and creating new products to maintain competitive parity, and centralizing to retain control while simultaneously decentralizing to encourage the contributions of autonomous, self-managed professionals to the embryonic corporate culture. Rapidly growing firms are challenged to strike a balance between these multiple pulls when designing their managerial systems.